Telemedicine for Outpatients: A Case Study of the First Experience with Diabetic Patients in the Local Health Authority of Modena - Perrone, Francesca Annamaria; Pederzini, Lucia; Casoni, Federica; Artoni, Paola; Guidetti, Fausta; Vescovini, Cristina; Semeraro, Valentina; Gaetti, Emilia; Vinceti, Marco; Palandri, Lucia; Righi, Elena (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. During the COVID-19 pandemic, telemedicine had the opportunity to demonstrate its potential. In Italy, after an initial period of mistrust, it became clear that remote medicine can provide significant benefits for both healthcare professionals and patients. In the Local Health Unit of Modena (Emilia Romagna region, Northern Italy), great importance was placed on developing, promoting, and managing all telemedicine activities. In particular, it was decided to prioritize the activation of tele- visit services in accordance with the guidelines of the Emilia-Romagna region. Study Design. This case study aims to illustrate the activities planned and developed at the Local Health Authority of Modena for the implementation of the first service of this kind, the tele-visit service for outpatients suffering from type 1 diabetes mellitus, and to analyze data from the first 12 months of activity (from May 2023 to April 2024) to share reflections on the strengths and critical points encountered. Method. For the activation of tele-visits at the Local Health Authority of Modena, a dedicated working group was established with the mandate to manage all clinical, organizational, and IT aspects. Before starting the service, various preliminary activities were carried out, including selecting the clinical specialty to be activated, defining patient inclusion criteria, implementing IT systems, assessing clinical risks, preparing and distributing information materials, training healthcare personnel, and planning outpatient activities. Results. During the first year of experimental activation of the service (May 2023–April 2024), a total of 72 patients were enrolled in the project, with 103 tele-visits provided. The patients were predominantly women (67%), and the most represented age groups were 30–39 (26%) and 40–49 (21%). Half of the specialists in the Diabetology Service (9/19) participated in the initiative by providing tele-visits, most of whom were young and all of whom were women. The main issues identified through regularly scheduled meetings with professionals, to which the working group is seeking the most appropriate solutions, include poor adherence by many patients who still have doubts about this modality, the habit of many patients rescheduling appointments multiple times, a habit not diminished by this visit method, the non-uniform adherence of professionals, and uneven territorial diffusion of the service. Lastly, professionals reported various IT difficulties. Although the number of tele-visits was not high, the initiative has sparked the interest of several specialists, some of whom have already proposed activating other telemedicine services, with some even suggesting innovative new projects. The next steps will involve extending diabetes monitoring to pregnant women with gestational diabetes and developing tele-visit services for endocrinology, neurology, hematology, and gastroenterology. Conclusions. Implementing a tele-visit service in a Local Health Unit is a complex process. A thorough evaluation of the issues that emerged during the development phases and the initial delivery period can help us to act proactively to prevent the failure of future projects. Our evaluations suggest a need to act on two fronts: on one hand, we must organize further activities to promote telemedicine to both patients and healthcare providers, while on the other hand, we must work to resolve IT issues.